QUick Count Analisis Akurasi dan Efisiensi pada Quick Count Menggunakan Ambang MinMax - Riadi Marta Dinata (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2023)
Quick Count is a method of quickly calculating general election results using data from a sample of polling stations (TPS), which are selected randomly and proportionally. In this research, researchers propose the Minmax Quick Count approach to Simple Random Sampling (SRS) to find the optimal sampling technique. Namely to find a comparison of accuracy and efficiency between Primary-SRS against SRS using Minimum and Maximum voter vote thresholds. The quick count case study is the DKI DKI Jakarta area, using validated test data